George Thomson Esqr. - Cochran, John, active 1821-1865 (engraver):::Creator::::::::::::; Raeburn, Henry, Sir, 1756-1823 (artist):::Contributor:::::::::::: (Blackie & Son)
Engraving of the Scottish publisher George Thomson